2014
DOI: 10.1179/1743284713y.0000000339
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Co substitution for La on hydrogen storage properties and thermal stabilities of amorphous Mg60Ni30La10−xCox (x = 0, 2 and 4) alloys prepared by melt spinning

Abstract: A comparison of the hydrogen storage properties and thermal properties of amorphous Mg60Ni30La10−xCox hydrogen storage alloys prepared by melt spinning has been investigated. A, B and C were used to represent each alloy composition when x = 0, 2 and 4 respectively. Their microstructures, the hydrogen storage properties and the thermal stabilities were analysed by X-ray diffraction (XRD), PCTPro2000 and differential scanning calorimetry (DSC) respectively. After hydrogenation of Mg60Ni30La10−xCox (A, B and C) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Of the various energy conversion and storage materials that have been developed over recent years, amorphous composites based on a La-Mg system alloy that is combined with Ni powder by mechanical milling are considered amongst the most promising, by virtue of their high electrochemical discharge capacity [1][2][3]. Indeed, Y. Wang and X. Wang [4] have already demonstrated that the ball milling of Pr 5 Mg 41 with 200 wt.% Ni can achieve an excellent electrochemical hydrogen storage capacity, reaching as high as 1016.2 mAh/g.…”
Section: Introductionmentioning
confidence: 99%
“…Of the various energy conversion and storage materials that have been developed over recent years, amorphous composites based on a La-Mg system alloy that is combined with Ni powder by mechanical milling are considered amongst the most promising, by virtue of their high electrochemical discharge capacity [1][2][3]. Indeed, Y. Wang and X. Wang [4] have already demonstrated that the ball milling of Pr 5 Mg 41 with 200 wt.% Ni can achieve an excellent electrochemical hydrogen storage capacity, reaching as high as 1016.2 mAh/g.…”
Section: Introductionmentioning
confidence: 99%
“…High discharge capacity and remarkable capacity retention even after 3 years greatly increase the actual performance of these Ni-MH batteries in mobile devices. Due to the high thermodynamic stability of their hydrides and an inert passive layer on the surface, the Mg based alloys such as MgH 2 , Mg 2 Ni, Mg 60 Ni 30 La 102x Co x , CeMg 12 z100%Ni, Mg-LaNi 5 [1][2][3] suffer from poor hydrogen absorption and desorption rates at the ambient temperatures, hence inhibiting the application of these alloys in Ni-MH. Therefore, A 2 B 7 type La-Mg-Ni based hydrogen storage alloy has nowadays become the best choice to manufacture this kind of Ni-MH battery.…”
Section: Introductionmentioning
confidence: 99%